A Review: Neurotoxicity of Doxorubicin - Hanan Saadon; Noor Abd Alkhudhur Salman (مجلة علوم ذي قار)
Although, Doxorubicin an effective chemotherapeutic agent, has been associated with significant neurotoxic effects, impacting the nervous system. This neurotoxicity can lead to various neurological complications, including cognitive impairments, neuropathic pain, and motor dysfunction. The neurotoxic effects of Doxorubicin are attributed to several mechanisms, including oxidative stress, inflammation, neuroinflammation and apoptosis of neuronal cells. These pathways become even more complex when multiple drugs are used simultaneously or in a fixed sequence, which is often the case in combination chemotherapy brain damage. Further research is needed to elucidate the precise mechanisms underlying doxorubicin-induced neurotoxicity and explore potential protective agents. In addition, studies focusing on long-term neurological outcomes in cancer survivors treated with doxorubicin are warranted. Developing neuroprotective agents or alternative treatment regimens or  using nanocomposites that reduce the neurotoxic effects while maintaining the efficacy of doxorubicin is a very important area for future investigation.